2022
DOI: 10.2217/fon-2022-0022
|View full text |Cite
|
Sign up to set email alerts
|

Application of Cherenkov Radiation in Tumor Imaging and Treatment

Abstract: Cherenkov radiation (CR) is the characteristic blue glow that is generated during radiotherapy or radioisotope decay. Its distribution and intensity naturally reflect the actual dose and field of radiotherapy and the location of radioisotope imaging agents in vivo. Therefore, CR can represent a potential in situ light source for radiotherapy monitoring and radioisotope-based tumor imaging. When used in combination with new imaging techniques, molecular probes or nanomedicine, CR imaging exhibits unique advanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 116 publications
0
4
0
Order By: Relevance
“…These limitations could be overcome by Cherenkov light (CL), which can be produced by diagnostically or therapeutically used radioisotopes (e.g., Ga-68, Re-188, or Y-90) [ 4 , 5 , 6 ]. CL is already used diagnostically, for example, in visual imaging [ 3 , 7 , 8 , 9 ]. This features a new therapeutic approach: depositing phototoxic substances inside the tumor and activating these via CL in addition to internal or external irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…These limitations could be overcome by Cherenkov light (CL), which can be produced by diagnostically or therapeutically used radioisotopes (e.g., Ga-68, Re-188, or Y-90) [ 4 , 5 , 6 ]. CL is already used diagnostically, for example, in visual imaging [ 3 , 7 , 8 , 9 ]. This features a new therapeutic approach: depositing phototoxic substances inside the tumor and activating these via CL in addition to internal or external irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitizing or synergistic effects of AuNPs in radiation therapy have been investigated using in vitro studies with X-rays, γ-rays, electron beams, and high-energy charged protons/carbon ions. In a study, the results showed that AuNPs could produce sensitization and synergistic effects in radiotherapy using different types of radiation [22][23][24][25]. In a major advance in 2022, Mzwd et al [26] used a green technique for nanoparticle synthesis.…”
Section: Gold-based Nanoparticlesmentioning
confidence: 99%
“…The potential and synergistic impact of AuNPs in radiation therapy have been explored in in vivo studieds by using X-rays, γ-rays, electron beams, as well as high-energy charged protons and carbon ions. AuNPs could induce sensitization and synergistic effect in radiotherapy by means of various types of radiation. , In another study, Mzwd and his group synthesized nanoparticles using green synthesis of stable AuNPs in gum Arabic (GA) solution via laser ablation technique as a CT contrast agent and assert that CT image numbers amplified as the concentration of GA-AuNPs increased . This indicates the potential ability of GA-AuNPs as contrasting agents.…”
Section: Nanoparticles Used For Theranostic Purposesmentioning
confidence: 99%